AGRIBISNIS PADI SAWAH DI KECAMATAN MEDANG DERAS KABUPATEN BATU BARA - Panjaitan, Pardomuan Hotmauli; Hadi, Syaiful; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the agribusiness system in the district of paddy in the Medang Deras subdistrict and determine farm income paddy in the Medang Deras subdistrict. This research conducted by survey method where samples were taken by 30 respondents in each village have taken 10 respondents farmers besides 2 collectors an 2 tauke besides. The results showed that the provision  of means of productions do not meet the proper criteria 6.Cost of rice production in one growing season of Rp.10.361.917,2/hektare pee planting season variable costs of Rp.8.091.891,4/ hectar.The  rice production amounted to 4.444,60 kg / hectare pee planting season.Gross income op Rp.20.81.,877,1/hectare and the clean income is Rp.10.450.960,0/ hectare in one season with the RCR at 2,01. Rice sold by the farmers onlyin the form of wet rice crop (GBP) and dry grain harvest (GKP) with one channel only, namely farmers, collectors and wholesalers. Institutional farming support (credit invidual farming ), education and training as well as the information can not be accessed by either.  Keywords:Agribusiness,Rice paddy.